1981
DOI: 10.1080/0360127810070109
|View full text |Cite
|
Sign up to set email alerts
|

Healthy, Happy, and Old: Children Learn About the Elderly

Abstract: This study explored the effectiveness of a curriculum in fostering children's positive attitudes toward the elderly and their own aging. The curriculum was developed around three major goals: (1) increasing children's knowledge of the elderly; (2) enabling children to assess their own aging positively; and (3) decreasing negative stereotyping of the physical and behavioral characteristics of the elderly. A total of 108 children in kindergarten through the sixth grade received the curriculum; 107 children in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Types of intervention programs that have resulted in positive attitude change toward old people include: (a) oral history projects (Myerhoff & Tufte, 1975); (b) elder volunteer programs (Carstensen, Mason, & Caldwell, 1982); and (c) open-ended intergenerational discussions (Labouvie-Vief & Baltes, 1976;Olejnik & LaRue, 1981;Seefeldt et al, 1981;Trent, Glass, & Crockett, 1979).…”
mentioning
confidence: 97%
“…Types of intervention programs that have resulted in positive attitude change toward old people include: (a) oral history projects (Myerhoff & Tufte, 1975); (b) elder volunteer programs (Carstensen, Mason, & Caldwell, 1982); and (c) open-ended intergenerational discussions (Labouvie-Vief & Baltes, 1976;Olejnik & LaRue, 1981;Seefeldt et al, 1981;Trent, Glass, & Crockett, 1979).…”
mentioning
confidence: 97%
“…Waas, Fillmer, and Ward (1981) found negative stereotyping of older persons as a hurdle in implementing the Older Americans Act. Seefeldt, Jantz, Galper, and Serock (1981) tested a 6-week curriculum on aging to promote positive attitudes toward the elderly among kindergarten through sixth grade (K-6) students. The ündings revealed that although attitudes toward the elderly improved, the children did not develop positive images about their own aging process.…”
Section: Im P Ac T Of Sc H Ool P R Ojec Ts On C H Ild R En's Attitud Esmentioning
confidence: 99%
“…Need for the Study "People in the United States, as people everywhere, are ambivalent about aging" ( de Beauvoir, 1973in Seefeldt et al, 1981). Yet, "between today and the year 2050, the percentage of persons age 65 and older will rise from the current twelve percent of the total population to 23 percent of the total population" (Aaina America.…”
Section: What Are the Guidelines For A Successful Intergenerational Pmentioning
confidence: 99%
“…Neugarten (1971( , in Seefeldt et al 1981 explained, "stereotypes about aging and the aged create a particularly complex set of problems. In addition to making us fear aging, the stereotypes lead to a divisiveness in society at large that has been called ageism--that is negative or destructive competition" (p. 80).…”
Section: What Are the Guidelines For A Successful Intergenerational Pmentioning
confidence: 99%
See 1 more Smart Citation